2010
DOI: 10.1021/jm901913s
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-Phenyl-4-(thiazol-5-yl)pyrimidin-2-amine Aurora Kinase Inhibitors

Abstract: Through cell-based screening of our kinase-directed compound collection, we discovered that a subset of N-phenyl-4-(thiazol-5-yl)pyrimidin-2-amines were potent cytotoxic agents against cancer cell lines, suppressed mitotic histone H3 phosphorylation, and caused aberrant mitotic phenotypes. It was subsequently established that these compounds were in fact potent inhibitors of aurora A and B kinases. It was shown that potency and selectivity of aurora kinase inhibition correlated with the presence of a substitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 74 publications
2
51
0
Order By: Relevance
“…Our interest in the development of kinase inhibitors has resulted in a number of clinical and pre-clinical drug candidates [21][22][23][24][25][26]. We have now discovered another novel class of 2,4,5-trisubstituted pyrimidine CDK inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in the development of kinase inhibitors has resulted in a number of clinical and pre-clinical drug candidates [21][22][23][24][25][26]. We have now discovered another novel class of 2,4,5-trisubstituted pyrimidine CDK inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…N-phenyl-4-(thiazol-5-yl)pyrimidin-2-amine derivatives (Fig. 10) [130], with a similar structure to Dasatinib, have been described as potent aurora kinase inhibitors. However, they were not active against serine/threonine protein kinases A, B, and C (PKA, Akt/PKB, PKC) extracellular signal-regulated kinase-2 (ERK2).…”
Section: Thiazole Derivativesmentioning
confidence: 99%
“…In this paper, we considered the compound CYC116 ( [19,20]). It has previously been shown that CYC116 inhibits both AK-A and AK-B and it is thought that its main cite of action is the spindle assembly checkpoint.…”
Section: Modelling the Dynamic Effects Of Drug Dose On Multi-cellularmentioning
confidence: 99%